D.I. Meyer about the essence of the property right and its constituent parts - Z.A. Akhmetyanova; O.N. Nizamieva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper presents D.I. Meyer’s views on ownership, which is considered to be the most important property right for the civil turnover, and on its traditional contents, including powers of possession, use, and disposal. Special attention has been paid to D.I. Meyer’s idea that including the right to protect the property in the content of ownership as a fourth component is unnecessary, because it is already involved in the concept of law itself, and any possible action of the owner regarding the property can be reduced to possession, use, and disposition. Such characteristics of ownership as legal domination, property of completeness, and measure of freedom (limitation) have been discussed, whereas the right itself has been considered as the relationship of a person to a thing. In addition to the possible manifestations of the component parts of the property rights, possible restriction of powers and restrictions of the property rights in general have been considered. According to D.I. Meyer, limitations can be related both to the subject of ownership and to any part included in it. Besides the analysis of the thoughts of the leading civil law scholar about the essence of the subjective property rights, his position in terms of the current Russian legislation has been discussed.